Multisensory constraints on awareness. - Deroy, O; Chen, Y; Spence, C (Royal Society of London, 2014)
Given that multiple senses are often stimulated at the same time, perceptual awareness is most likely to take place in multisensory situations. However, theories of awareness are based on studies and models established for a single sense (mostly vision). Here, we consider the methodological and theoretical challenges raised by taking a multisensory perspective on perceptual awareness. First, we consider how well tasks designed to study unisensory awareness perform when used in multisensory settings, stressing that studies using binocular rivalry, bistable figure perception, continuous flash suppression, the attentional blink, repetition blindness and backward masking can demonstrate multisensory influences on unisensory awareness, but fall short of tackling multisensory awareness directly. Studies interested in the latter phenomenon rely on a method of subjective contrast and can, at best, delineate conditions under which individuals report experiencing a multisensory object or two unisensory objects. As there is not a perfect match between these conditions and those in which multisensory integration and binding occur, the link between awareness and binding advocated for visual information processing needs to be revised for multisensory cases. These challenges point at the need to question the very idea of multisensory awareness.